Variations in Elite Female Soccer Players' Sleep, and Associations With Perceived Fatigue and Soccer Games - Moen, Frode; Olsen, Maja; Halmøy, Gunvor; Hrozanova, Maria (Frontiers in Sports and Active Living, 2021)
The current study investigated the associations between female elite soccer players’ perceived fatigue and their sleep, and the associations between players’ sleep and soccer games. The sample included 29 female elite soccer players from the Norwegian national soccer team with a mean age of ~26 years. Perceived fatigue and sleep were monitored over a period of 124 consecutive days. In this period, 12.8 ± 3.9 soccer games per player took place. Sleep was monitored with an unobtrusive impulse radio ultra-wideband Doppler radar (Somnofy). Perceived fatigue was based on a self-report mobile phone application that detected daily experienced fatigue. Multi-level analyses of day-to-day associations showed that, firstly, increased perceived fatigue was associated with increased time in bed (3.6 ± 1.8 min, p = .037) and deep sleep (1.2 ± 0.6 min, p = .007). Increased rapid eye movement (REM) sleep was associated with subsequently decreased perceived fatigue (-0.21 ± 0.08 arbitrary units [AU], p = .008) and increased respiration rate in non-REM sleep was associated with subsequently increased fatigue (0.27 ± 0.09 AU, p = .002). Secondly, game night was associated with reduced time in bed (-1.0 h ± 8.4 min, p = < .001), total sleep time (-55.2 ± 6.6 min, p = < .001), time in sleep stages (light: -27.0 ± 5.4 min, p = < .001; deep: -3.6 ± 1.2 min, p = .001; REM: -21.0 ± 3.0 min, p = < .001), longer sleep onset latency (3.0 ± 1.2 min, p = .013) and increased respiration rate in non-REM sleep (0.32 ± 0.08 respirations per min, p = < .001), compared to the night before the game. The present findings show that deep and REM sleep, and respiration rate in non-REM sleep, are key indicators of perceived fatigue in female elite soccer players. Moreover, sleep is disrupted during game night, likely due to the high physical and mental loads experienced during soccer games. Sleep normalizes during the 1st and 2nd night after soccer games, likely preventing further negative performance-related consequences.